Transatlantische Beziehungen: Das Ende einer wunderbaren Freundschaft? - Schmidt, Ingo (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2003)
After World War II US-hegemony has been unchallenged in the capitalist part of the world. Therefore the US could afford to promote European integration. Meanwhile the economic foundations of the US' position have been weakened. First the superiority in terms of productivity got lost and after the New Economy boom there are also doubts about US-dominance on financial markets. This is the more so since the introduction of the Euro represents a major challenge for the Dollar. Nevertheless transatlantic competition on economic issues may not lead to a split as ruling classes in Europe and America share common interests against the rest of the world.